An Update At The Interface Between Infectious Pathology And The Stomatognathic System - Carmen Dorobăţ; Carmen Manciuc; Gheorghe Dorobăţ; Andrei Vâţă (Romanian Society of Oral Rehabilitation, 2013)
The stomatognathic system normally hosts of an extremely diverse microbial flora responsible for the anti-infectious defence, but which, preponderantly in some special categories of patients, through dissemination or toxin release, may have an unfavourable influence on patients' health state. Both dental patients and medical staff are exposed, due to direct contact with mucus and secretions of the stomatognathic system, to a great number of non-bacterial pathogens, such as hepatitis virus B or C, Epstein-Barr virus, herpes simplex virus 1 or 2, HIV, fungi, which colonize, infect or are just expressed at this level. A large series of infectious diseases have primary or secondary manifestations located in the area of the stomatognathic system, and a well-trained medical personnel can decisively contribute to avoid the spreading or aggravation of infection, by setting an early diagnose or an adequate treatment.